2006
DOI: 10.1007/s10096-006-0170-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of Q fever in humans, ruminant animals, and ticks in Cyprus using a geographical information system

Abstract: A cross-sectional study of Q fever was conducted in a representative sample of the human and animal population in Cyprus in order to assess the seroprevalence of Q fever and the prevalence of related risk factors. A total of 583 human and 974 ruminant animal serum samples were collected and tested for the detection of antibodies against Coxiella burnetii phase II antigen using an indirect immunofluorescent assay. One hundred forty-one ticks were collected from the infested animals examined; the polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 68 publications
8
64
1
1
Order By: Relevance
“…Previous studies have shown that ticks seem to play an important role in the dissemination of bacteria in animals, especially wild, believing it to be an important factor in the transmission to domestic animals (Psaroulaki et al, 2006). On the other hand, a recent study developed in the Netherlands, after three years of an outbreak of Q fever, researchers investigated the role ticks play in the transmission C. burnetii, showing that actual risk of this infection by ticks is negligible.…”
Section: Query Fever (Q Fever)mentioning
confidence: 99%
“…Previous studies have shown that ticks seem to play an important role in the dissemination of bacteria in animals, especially wild, believing it to be an important factor in the transmission to domestic animals (Psaroulaki et al, 2006). On the other hand, a recent study developed in the Netherlands, after three years of an outbreak of Q fever, researchers investigated the role ticks play in the transmission C. burnetii, showing that actual risk of this infection by ticks is negligible.…”
Section: Query Fever (Q Fever)mentioning
confidence: 99%
“…Cattle, sheep and goats are the main sources of infection in humans [3,4]. Infected animals excrete C. burnetii into the environment via birth products such as the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…A third reason for underestimation of chronic Q fever cases is the possibility that we overestimated the number of past C. burnetii infections by using a detection cutoff titer of Ն1:32 for phase I and II IgG. These titers can also be caused by antibodies cross-reacting to other pathogens or by aspecific reactions (18). Yet, it is also known that, following C. burnetii infection, antibodies to C. burnetii can disappear over time or titers can become very low, leading to an underestimation of the infection rate (12,25).…”
Section: Discussionmentioning
confidence: 99%